TOLERANT ATTITUDES TOWARDS PERSONS WITH SPECIAL EDUCATIONAL NEEDS AS A COMPONENT OF PROFESSIONAL TRAINING FOR TEACHERS IN HIGHER EDUCATION INSTITUTIONS - Kolosova, Olena; Sarancha, Iryna; Pylypenko, Yaroslava; Khilya, Anna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2022)
One of the priorities of the modern educational process is the formation and creation of an inclusive space, which includes all components of universal design and, in particular, issues of staff preparedness. Thus, the basic training of specialists in this sphere includes not only the competence of teachers and professionals of helping professions in inclusion, but also the development of established personal attitudes and judgments in accordance with the values of the modern world. Of particular importance is the development of tolerance in future teachers in all aspects of its manifestation - both in the process of learning in higher educational institutions, during the internship, and in the process of professional activity itself, in particular during communication and interaction with persons with special educational needs. The importance of this aspect in a teacher's professional profile prompted us to study this quality and determine the level of tolerant attitude of future specialists to children with special educational needs. To solve this problem, we used a number of methods that allowed us to comprehensively study the personal qualities of students in academic groups where students with special educational needs or who received experience in communicating with children with special educational needs during internship in specialized educational institutions or social welfare institutions. Thus, to analyze the qualitative aspects of tolerance (ethnic, social, personal), we used the express questionnaire “Tolerance Index” (Soldatova, Kravtsova, Khukhlaev, Shaigerova, 2002); In order to study the value and semantic component of students' tolerant attitudes we used the “Tolerance Diagnostics. Incomplete sentences” (Kuhareva, 2013); in research of the emotional-volitional component - the method “The Balanced Emotional Empathy Scale. BEES” (Mehrabian, Epstein, 2000); for the analysis of the communicative component – the test of communicative tolerance (Boyko, 2009).Besides, the listed methods and test were supplemented with the inclusive education questionnaire and the author's art-therapy techniques on the perception of persons with special educational needs and understanding of the importance of tolerant communication within professional activities. This approach in the research has allowed us to review essentially the basic educational components for the formation of professional and inclusive competences on the basis of tolerant attitude, to form and briefly outline in this scientific review our own methodological proposal for the introduction of training and other innovative forms of building interaction in academic groups.